Effect of Stress Management in Over-weight and Obese Women - Kotwani, Dr Shweta; Mehta, Dr. Amita (International Journal of Innovative Research in Medical Science, 2019)
Keywords: obesity, stress management, relaxation, PMR, Diaphragmatic breathing, over-weight women, BMI.